Validating the Brain Injury Guidelines: Results of an American Association for the Surgery of Trauma prospective multi-institutional trial. Issue 2 (28th August 2022) - Joseph, Bellal; Obaid, Omar; Dultz, Linda; Black, George; Campbell, Marc; Berndtson, Allison E.; Costantini, Todd; Kerwin, Andrew; Skarupa, David; Burruss, Sigrid; Delgado, Lauren; Gomez, Mario; et al.
Abstract : The Brain Injury Guidelines are safe and effectively guide the management of traumatic brain injury patients, leading to reduced healthcare resource utilization, including hospital admissions, repeat imaging, and neurosurgical consultation. Abstract : INTRODUCTION: Brain Injury Guidelines (BIG) was developed to effectively use health care resources including repeat head computed tomography (RHCT) scan and neurosurgical consultation in traumatic brain injury (TBI) patients. The aim of this study was to prospectively validate BIG at a multi-institutional level. METHODS: This is a prospective, observational, multi-institutional trial across nine Levels I and II trauma centers. Adult (16 years or older) blunt TBI patients with a positive initial head computed tomography (CT) scan were identified and categorized into BIG 1, 2, and 3 based on their neurologic examination, alcohol intoxication, antiplatelet/anticoagulant use, and head CT scan findings. The primary outcome was neurosurgical intervention. The secondary outcomes were neurologic worsening, RHCT progression, postdischarge emergency department visit, and 30-day readmission. RESULTS: A total of 2, 432 patients met the inclusion criteria, of which 2, 033 had no missing information and were categorized into BIG 1 (301 [14.8%]), BIG 2 (295 [14.5%]), and BIG 3 (1, 437 [70.7%]). In BIG 1, no patient worsened clinically, 4 of 301 patients (1.3%) had progression on RHCT with no change in management, and none required neurosurgical intervention. In BIG 2, 2 of 295 patients (0.7%) worsened clinically, and 21 of 295 patients (7.1%) had progression on RHCT. Overall, 7 of 295 patients (2.4%) would have required upgrade from BIG 2 to 3 because of neurologic examination worsening or progression on RHCT, but no patient required neurosurgical intervention. There were no TBI-related postdischarge emergency department visits or 30-day readmissions in BIG 1 and 2 patients. All patients who required neurosurgical intervention were BIG 3 (280 of 1, 437 patients [19.5%]). Agreement between assigned and final BIG categories was excellent ( κ = 99%). In this cohort, implementing BIG would have decreased CT scan utilization and neurosurgical consultation by 29% overall, with a 100% reduction in BIG 1 patients and a 98% reduction in BIG 2 patients. CONCLUSION: Brain Injury Guidelines is safe and defines the management of TBI patients by trauma and acute care surgeons without the routine need for RHCT and neurosurgical consultation. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :